Targeting B and T Lymphocyte Attenuator Regulates Lupus Disease Development in NZB/W Mice - Gherardi L; Aubergeon L; Sayah M; Fauny JD; Dumortier H; Monneaux F (ImmunoTargets and Therapy)
Léa Gherardi,* Lucie Aubergeon,* Mélanie Sayah, Jean-Daniel Fauny, Hélène Dumortier, Fanny Monneaux CNRS UPR3572, Immunology, Immunopathology and Therapeutic Chemistry, Institute of Molecular and Cellular Biology, Strasbourg, 67084, France*These authors contributed equally to this workCorrespondence: Fanny Monneaux, CNRS UPR3572, Institut de Biologie Moléculaire et Cellulaire, 2 Allée Konrad Roentgen, Strasbourg, 67084, France, Email f.monneaux@ibmc-cnrs.unistra.frPurpose: The co-inhibitory receptor B and T Lymphocyte Attenuator (BTLA) negatively regulates B and T cell activation. We have previously shown an altered BTLA expression by regulatory T cells and an impaired capacity of BTLA to inhibit CD4+ T cell activation in lupus patients. In this study, we analyzed BTLA expression and function in the NZB/W lupus-mouse model and examined the therapeutic potential of BTLA targeting.Methods: BTLA expression and function were analyzed in young (10– 12-week-old) and old-diseased NZB/W mice (> 35-week-old with proteinuria) in comparison to age-related BALB/W control mice. 20– 22 weeks old NZB/W mice (n=10) were injected i.p with 3 mg/kg, twice a week for ten weeks, with the anti-BTLA antibody 6F7 or its isotype control.Results: In old-diseased NZB/W mice, BTLA expression is slightly modified in B cell subsets whereas CD4+ T cells display impaired BTLA functionality. Administration of the 6F7 anti-BTLA antibody into 20– 22 week-old NZB/W mice resulted in a delayed onset of proteinuria (p< 0.01), limited kidney damages (p< 0.05) and an increased survival rate (p< 0.01) compared to isotype-treated mice. This beneficial effect was associated with a decrease in circulating B cell and spleen follicular B cell numbers. Regarding its mode of action, we demonstrated that the 6F7 antibody is not a depleting antibody and does not block HVEM binding to BTLA, but instead induces BTLA down modulation and exhibits in vivo agonist activity.Conclusion: Overall, our data confirm the involvement of BTLA in lupus pathogenesis and provide the first evidence that BTLA is a potential therapeutic target for the treatment of lupus.Keywords: systemic lupus erythematosus, BTLA, lupus mice, inhibitory receptors